If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 6(5) = 8 Multiply 6 * 5 y + 30 = 8 Reorder the terms: 30 + y = 8 Solving 30 + y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + y = 8 + -30 Combine like terms: 30 + -30 = 0 0 + y = 8 + -30 y = 8 + -30 Combine like terms: 8 + -30 = -22 y = -22 Simplifying y = -22
| y+6(-1)=8 | | w^2=5w+24 | | p^2-8p-96=0 | | 3(a-10)=33 | | 3b+(b-2)+5a= | | 3a+(4a+5b)= | | 3a+(4a+56)= | | 203-4x=32x+19 | | 5(y+7)=45 | | 2x/5=6x/5+6 | | 6(4x+2)= | | -40+2y=-3y | | Factorisex^2+2x-24=0 | | x-1/4x=24 | | 5x+(x-1)=0 | | 8-x=2-4x | | 4x+3x-1=0 | | 4/X=X/3 | | 1/6f=12 | | 6T+8/1-T=3 | | 0.09m=1 | | 3(2x+1)=5x-2 | | 66-x=4x+26 | | y-2y=(y-2)(y+3) | | (7x-1)(0.4x-4)=0 | | 4abc-4ab= | | 8x^4+12x^3+20x=0 | | X^2+20x+60=0 | | 1/6x3 | | f(t)=t^4-3t^3-12t^2+t-6 | | 4(3x+2)-3(2x-1)=35 | | ln(9x^2-4)-ln(3x+2)=2 |